Dynamic Epistemic Logic with Assignments, Concurrency and Communication Actions - Benevides, Mario Folhadela; Lima, Isaque Macalam Saab (Anais do Workshop Brasileiro de Lógica (WBL); 2020: Anais do I Workshop Brasileiro de Lógica, 2020)
This work proposes an extension of Dynamic Epistemic Logic with Communication Actions by adding the notion of postconditions from Dynamic Epistemic Logic with Assigments to deal with boolean assignments to action models. Other concurrent logics, like Concurrent Epistemic Action Logic introduced by Ditmarsch, Hoek and Kooi, do not deal with boolean assignments. We present an axiomatization and show that the proof of soundness, completeness and decidability can be done using a reduction method.